Comparison of Wet and Dry EEG Electrodes Based On Brain Signals Characterization In Temporal and Anterior Frontal Areas Using Audio Stimulation. (March 2020) - Faadhilah Afif, Nur; Harke Pratama, Sra; Haryanto, Freddy; Nurul Khotimah, Siti; Suprijadi,
Abstract: Electroencephalography (EEG) electrodes are divided into two types: dry and wet. In wet electrodes, a gel or saline liquid is used to increase the conductivity value, however, it tends to dry over time. On the contrary, gel or saline liquid is not required on the dry electrode. The use of certain types of electrode in EEG influences Power Spectral Density (PSD) of brain signals. Therefore, this study compared the EEG signal produced by Emotiv using the two different types of electrodes and a specific stimulus. This study was conducted using Emotiv EPOC (wet) and Insight (dry). The Temporal (T7 and T8) and Anterior Frontal (AF3 and AF4) electrodes from both devices were used to be compared. An audio stimulus that contains a story was chosen followed by a small task related to the story. The data acquisition was performed in 36 minutes to maintain the stability of the two types of electrodes. Three minutes of recordings in resting condition were conducted on both before and after given audio stimulus. Audio stimulation followed by a small task was performed for thirty minutes. The data analysis has consisted of EEG data pre-processing using centering and filtering the data, followed by PSD calculation using the Welch periodogram with Hanning window. The result showed that the decrement percentage of PSD after stimulation from wet was higher than dry electrodes.